Mapping the Physical Conditions of the Region as an Effort for Tsunami Disaster Mitigation in Moa Lakor District, Southwest Maluku Regency, Maluku Province - Rakuasa, Heinrich; Sihasale, Daniel Anthoni (GEOFORUM, 2023)
The geographical conditions of Moa Lakor District, Southwest Maluku Regency, located within the Ring of Fire, with relatively flat topography and high population density in coastal areas, make Moa Lakor District highly susceptible to tsunami disasters in Maluku Province. This study aims to map the physical conditions of the region in an effort to mitigate tsunami disasters in Moa Lakor District, Southwest Maluku Regency, Maluku Province. The physical condition data used in this study include land elevation, slope gradient, and distance from the coast. These three variables were assigned scores and weights, which were then overlaid to produce a tsunami hazard map and identify affected built-up areas. The results indicate that the high tsunami hazard class covers 65.35% of the area, totaling 23,534.71 hectares. The medium hazard class covers 7,852.43 hectares or 21.80%, and the low hazard class covers 4,627.39 hectares or 12.85%. The built-up land predicted to be in the high hazard zone covers 738.33 hectares, in the medium hazard zone covers 162.98 hectares, and in the low hazard zone covers 56.52 hectares.